ATHENA: Contributing to Development of Higher Education Institutions for the Digital Age - J. C. Quadrado; Yu. P. Pokholkov; K. K. Zaitseva (Moscow Polytechnic University, 2021)
Facilitated by public administrations and the European Union, higher education institutions should support their teachers so they develop the skills for online and other forms of teaching and learning opened up by the digital era and should exploit the opportunities presented by technology to improve the quality of teaching and learning. The article focuses on new European Union grant programs that empower the increasing of digital literacy in the higher education area, developing cooperation, and overcoming challenges during the coronavirus pandemic. This initiative can empower a new European University and support an international project aimed at certification of professional educators with the participation of a Russian partner.